" n Kerklik-akademiese portret van B J van der Merwe (1926-1968): Deel Een - student en predikant - Venter, P. M. (Hervormde teologiese studies, 1999)
A pastoral-academical portrait of B J van der Merwe(1926-1968): Part one - student and minister. This first part deals with Van der Mervre's tertiary education, his year as church minister, as well as his preparation and study as doctoral student at the University of Groningen, Netherlands. The inluence of Van Selms, Cemserand Vriezen is discussed, as well as his first publications and his doctoral thesis.